A single protocol for extraction of gDNA from bacteria and yeast - Vingataramin, Laurie (BioTechniques, 2015)
Guanidine thiocyanate breakage of microorganisms has been the standard initial step in genomic DNA (gDNA) extraction of microbial DNA for two decades, despite the requirement for pretreatments to extract DNA from microorganisms other than Gram-negative bacteria. We report a quick and low-cost gDNA extraction protocol called EtNa that is efficient for bacteria and yeast over a broad range of concentrations. EtNa is based on a hot alkaline ethanol lysis. The solution can be immediately centrifuged to yield a crude gDNA extract suitable for PCR, or it can be directly applied to a silica column for purification